2022
DOI: 10.1111/1756-185x.14319
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of leflunomide as a steroid‐sparing agent in treatment of Indian giant cell arteritis patients: A 2‐year follow‐up study

Abstract: Giant cell arteritis (GCA) is characterized by chronic granulomatous inflammation of medium and large arteries with predilection for extra-cranial branches of the carotid arteries. GCA is considered as the most common type of primary vasculitis in the Western world; however, it is reported less frequently from the Indian subcontinent. 1,2 Ultrasonographic evaluation of superficial temporal arteries (STA) is becoming a common practice in the diagnosis of GCA because it

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…A recent prospective Indian observational study reported 22 patients newly diagnosed with cranial-only GCA with an add-on therapy with leflunomide to a predefined glucocorticoid regimen at week 0, demonstrating that the maintenance of continuous steroid-free remission was achieved in 68% of patients for a median follow-up period of 24 months ( 18 ). Seven (31.8%) patients in this cohort experienced a clinical relapse after a median of 12 months after initial remission, a rate significantly higher than in our cohort; however, due to the different design of the study and limited number of patients, a comparison is inapplicable.…”
Section: Discussionmentioning
confidence: 99%
“…A recent prospective Indian observational study reported 22 patients newly diagnosed with cranial-only GCA with an add-on therapy with leflunomide to a predefined glucocorticoid regimen at week 0, demonstrating that the maintenance of continuous steroid-free remission was achieved in 68% of patients for a median follow-up period of 24 months ( 18 ). Seven (31.8%) patients in this cohort experienced a clinical relapse after a median of 12 months after initial remission, a rate significantly higher than in our cohort; however, due to the different design of the study and limited number of patients, a comparison is inapplicable.…”
Section: Discussionmentioning
confidence: 99%
“…3 Non-glucocorticoid immunosuppressive agents (ie tocilizumab, methotrexate) can be used as adjunctive therapies in selected patients with GCA. 3,4 A recent prospective observational study by Das et al 5 showed the efficacy and safety of leflunomide as a steroid-sparing agent in patients with GCA.…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…53 A 2-year prospective observational study by Das et al found that all patients treated with leflunomide and a corticosteroid taper exhibited a clinical improvement and 77% could stop corticosteroids completely. 54 In fact, a recent retrospective study investigating 10 years' worth of medical records of patients with GCA from the United Kingdom found that patients who received leflunomide adjunctive therapy had better clinical outcomes than those who received corticosteroids alone. 55 Thus, leflunomide has shown potential as an adjunctive therapy in GCA, but RCTs are necessary to further assess and confirm the efficacy of leflunomide as a corticosteroid-sparing agent in GCA.…”
Section: Leflunomidementioning
confidence: 99%